Subcellular thiol functional group distribution in Geobacter sulfurreducens determined by Hg LIII-edge EXAFS - Meng, Fanchao; Skyllberg, Ulf; Li, Yangyang; Hayama, Shusaku; Björn, Erik; Song, Yu (Frontiers in Microbiology, 2026)
Mercury (Hg) is a global environmental concern due to its microbial conversion to methylmercury (MeHg), a potent neurotoxin that bioaccumulates in food webs and poses risks to ecosystems and human health. Thiol functional groups (RSH) play an important role in controlling Hg(II) speciation and bio-uptake in methylating bacteria, yet the spatial distribution and density of these thiols within cells remain largely unknown. We isolated subcellular fractions of the Hg methylating bacterium Geobacter sulfurreducens in the exponential growth phase, and used Hg LIII-edge EXAFS (Extended X-ray Absorption Fine Structure) to quantify thiols in the extracellular medium, inner and outer membranes, periplasm and cytoplasm. The whole-cell thiol content was determined to be 1.3 × 10−10 μmol cell−1. The inner membrane contributed 7.1 × 10−11 (53%), the outer membrane 1.2 × 10−11 (9%), the periplasm 3.6 × 10−11 (27%) and the cytoplasm 1.5 × 10−11 μmol cell−1 (11%). The extracellular fraction contributed an additional 5.7 × 10−11 μmol cell−1, corresponding to 30% of the thiols of the cell culture. Local thiol density (thiols normalized to TOC in individual compartment, RSH/TOC, μmol g−1 C) was 36, 450, 140, 600 and 29 μmol g−1 C in the cytoplasm, inner membrane, periplasm, outer membrane and extracellular fractions, respectively. EXAFS analyses demonstrate Hg-thiolate coordination across all compartments, with Hg-O/N bonding and elemental Hg0 formed at higher Hg loadings. In the periplasm, Hg-disulfide and traces of β-HgS were detected. The high thiol density at the membranes, relative to other compartments, may imply they have an important role in the retention and internalization of Hg(II). Periplasmic thiols may modulate Hg(II) transfer between membranes, and cytoplasmic thiols may regulate the intracellular availability of Hg(II) for methylation. This work provides the first compartment-resolved quantification of thiol abundances and densities in a model Hg-methylating bacterium at subcellular level, offering a mechanistic framework for understanding the speciation, bioavailability, and subcellular transformation of Hg(II) with relevance for other soft metals (e.g., Cd, Pb, Zn, Ag, and Cu).